Optimisation of supply chain management in an electronic commerce environment - Wu, Gang. (2008)
A supply chain consists of many entities interacting directly or indirectly to fulfil a customer’s request. There are five major drivers within the supply chain that determine its performance in terms of responsiveness and efficiency. These drivers are facilities, production, inventory, transportation and information. Supply chain management is a set of approaches utilised to efficiently integrate suppliers, manufacturers, warehouses, and stores, so that each merchandise is produced and distributed in the right quantities, to the right locations and at the right time, in order to minimize system-wide cost while satisfying service level requirements.